Analisis Fenomena Informed Consent: Tantangan dan Anomali bagi Dokter Muda di Jawa Timur - Meivy Isnoviana; Rinna Dwi Lestari; Nurkhamida Nurkhamida; Andra Agnes (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Clerkship who are studying at Network Hospital often deal directly with patients. Clerkships also learn to convey informed consent, which will determine the patient's willingness or refusal to perform the action. This study aims to determine clerkship' understanding of informed consent and how to convey it at the X Faculty of Medicine Network Hospital in East Java. This research method is a mixed-method sequential explanatory design. The population of this study was all clerkships who were studying at Hospital A and Hospital B using the total sampling method. The research instrument used a questionnaire on informed consent based on Permenkes No.290 Th 2008, which was validated. The data obtained were analyzed as univariate and bivariate and then combined with qualitative data based on FGD. Data will be presented in the form of tables and narrative text. It was found that the understanding of medium category informed consent was 50%, high and medium 20%, while for the delivery of informed consent in accordance with the ethical theory of the category was less than 45%, the medium category was 40%, and good was 12%. There is an anomaly where 19 respondents who are considered lacking in understanding turned out to be able to convey well. Shows that factors such as language, knowledge of disease, role models, and socio-culture are quite influential. Statistically, there is a relationship between the understanding and knowledge of clerkship in the delivery of informed consent, and overall factors such as language, educational background, knowledge of the patient's disease, and socio-culture have an important role in delivering informed consent effectively and ethically. Keywords: Clerkship, Understanding Informed Consent, Ethics of Informed Consent, Conveying Informed Consent  ABSTRAK Dokter muda yang sedang menempuh pendidikan di Network Hospital sering berhadapan langsung dengan pasien. Dokter muda juga belajar untuk menyampaikan informed consent, yang akan menentukan kesediaan atau penolakan pasien untuk melakukan tindakan. Penelitian ini bertujuan untuk mengetahui pemahaman dokter muda tentang informed consent dan cara menyampaikannya di Rumah Sakit Jaringan X Fakultas Kedokteran di Jawa Timur. Metode penelitian ini adalah metode desain campuran dengan penjelasan berurutan. Populasi penelitian ini adalah semuanya dokter muda yang sedang menempuh pendidikan di Rumah Sakit A dan Rumah Sakit B dengan menggunakan metode total sampling. Instrumen penelitian menggunakan kuesioner informed consent berdasarkan Permenkes No.290 Th 2008 yang telah divalidasi. Data yang diperoleh dianalisis menjadi univariat dan bivariat kemudian dikombinasikan dengan data kualitatif berdasarkan FGD. Penyajian data dalam bentuk tabel dan teks naratif. Ditemukan bahwa pengertian informed consent kategori medium adalah 50%, tinggi dan sedang 20%, sedangkan untuk penyampaian informed consent sesuai dengan teori etika kategori kurang dari 45%, kategori sedang adalah 40% dan baik adalah 12%. Terdapat anomali dimana diantara 19 responden yang dianggap kurang paham ternyata mampu menyampaikan dengan baik. Menunjukkan bahwa berbagai faktor seperti bahasa, pengetahuan tentang penyakit, panutan, dan sosial budaya cukup berpengaruh. secara statistik ada hubungan antara pemahaman dan pengetahuan dokter muda dalam pemberian informed consent, dan keseluruhan faktor seperti bahasa, latar belakang pendidikan, pengetahuan tentang penyakit pasien, sosial budaya memiliki peran penting dalam memberikan informed consent secara efektif dan etis. Kata Kunci: Dokter Muda, Pengertian Informed Consent, Etika Informed Consent, Penyampaian Informed Consent.